2015
DOI: 10.3389/fpsyg.2015.00010
|View full text |Cite
|
Sign up to set email alerts
|

Erratum on: The other-race and other-species effects in face perception—a subordinate-level analysis

Abstract: due to a typesetting error. This mistake does not change the scientific conclusions of the article in any way.The publisher apologizes for this error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…This is not surprising as negative symptoms and motor symptoms often correlate at a descriptive level in schizophrenia ( Walther and Strik, 2012 ), e.g. avolition contributes to reduced motor activity ( Docx et al, 2013 , Walther et al, 2015 ). In line with this, we found a strong correlation of the DSM-5 ratings for abnormal psychomotor behavior and negative symptoms in patients (see Table 2 ).…”
Section: Discussionmentioning
confidence: 98%
“…This is not surprising as negative symptoms and motor symptoms often correlate at a descriptive level in schizophrenia ( Walther and Strik, 2012 ), e.g. avolition contributes to reduced motor activity ( Docx et al, 2013 , Walther et al, 2015 ). In line with this, we found a strong correlation of the DSM-5 ratings for abnormal psychomotor behavior and negative symptoms in patients (see Table 2 ).…”
Section: Discussionmentioning
confidence: 98%
“…If threshold invariance is met, scalar or strong invariance can be assumed [ 53 ]. If strong measurement invariance could not be established, partial invariance was examined [ 52 , 54 ]. To test partial strong measurement invariance, first ill-specified items were identified by means of modification indices, then thresholds of these items were allowed to differ between groups.…”
Section: Methodsmentioning
confidence: 99%
“…They also failed to correctly use the Spanish graphemes /y/, /j/ and /g/ ( injectar for inyectar ). These results are extremely novel, given that there are no recent studies that have examined spelling disorders in OCPD prisoners, although Afonso et al ( 2015 ) and Suzuki and DeKeyser ( 2017 ) found that the word length effect affected dyslexics due to the cost of additional graphemic processing. In sum, it appears that people with OCPD and dyslexia make similar writing mistakes.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, those with writing difficulties have deficits in regulating mental operations in writing, which, in turn, leads to longer writing latencies, inter-letter intervals, and writing durations along with a greater number of orthographic errors, signs that are typical of dyslexia (Afonso et al, 2015 ; Nigro et al, 2015 ; Suzuki and DeKeyser, 2017 ; Nicolson and Fawcett, 2019 ). Dyslexia, however, is caused by multiple genetic and environmental risk factors as well as the interplay between them.…”
Section: Introductionmentioning
confidence: 99%